Thermosyphon Heat Sink Integrated Framework for CPU Cooling - Saroj Sharma (Journal of Power Electronics and Devices, 2016)
A warm model has been created to concentrate on the warm conduct of Thermosyphon incorporated Heat Sink amid CPU cooling. An Indirect cooling module has been tentatively considered and examined under relentless state condition for both regular and constrained convection. The warm model is utilized to decide the genuine heat exchange and the viability of the present model and contrasted it and the customary cooling technique and found that there is an apparent change in the present model.